Training of Future Civil Engineers in the Area of Foreign Language: Interaction of Educational Paradigms - Nordman Irina; Molodykh-Nagaeva Elena (MATEC Web of Conferences, 2017)
The article deals with problems of engineers’ training in higerh school. Problems in the organization of classroom and students’ independent work, in the area of evaluation and control as well as teaching recourses and training methods are pointed out. The role of foreign language in the training of future specialists in the field of construction is highlighted. The necessity of the use of settings of traditional and innovative educational paradigms when training of students in the specialization “Industrial and civil construction” on the discipline “Foreign Language” is proved. The interaction of traditional and innovative teaching resources, trraining methods, as well as evaluation and control means is shown. The conclusions on the effectiveness of interaction of traditional and innovative educational concepts when teaching a foreign language in technical universities are drawn.